2014
DOI: 10.1089/neu.2014.3331
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Oxidative Stress and 5-Lipoxygenase Activation by Edaravone Improves Depressive-Like Behavior after Concussion

Abstract: Brain concussions are a serious public concern and are associated with neuropsychiatric disorders, such as depression. Patients with concussion who suffer from depression often experience distress. Nevertheless, few pre-clinical studies have examined concussion-induced depression, and there is little information regarding its pharmacological management. Edaravone, a free radical scavenger, can exert neuroprotective effects in several animal models of neurological disorders. However, the effectiveness of edarav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
(71 reference statements)
0
12
0
4
Order By: Relevance
“…Regarding the therapeutic time window, a study found that edaravone can exert its effect when administered up to six hours after injury [ 65 ]. On the other hand, in a study on closed head injury, edaravone only exerted a significant effect when it was administered 1 h after injury, and the effect was dose-dependent [ 69 ].…”
Section: Therapeutic Options Targeting Oxidative Stress In Tbimentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the therapeutic time window, a study found that edaravone can exert its effect when administered up to six hours after injury [ 65 ]. On the other hand, in a study on closed head injury, edaravone only exerted a significant effect when it was administered 1 h after injury, and the effect was dose-dependent [ 69 ].…”
Section: Therapeutic Options Targeting Oxidative Stress In Tbimentioning
confidence: 99%
“…Additionally, the expression of Nrf2, a transcription factor, and its downstream genes were elevated by edaravone [ 65 ]. Similarly, in a mouse model of concussion, NT levels were decreased in the cortex and hippocampus when edaravone was administered [ 69 ]. In one study, H 2 O 2 level decreased, and SOD and GPx increased following edaravone treatment [ 70 ].…”
Section: Therapeutic Options Targeting Oxidative Stress In Tbimentioning
confidence: 99%
See 2 more Smart Citations
“…Many diverse clinical conditions as systemic infection, depression and stress have been shown to cause significant changes in oxidative balance. (Bhatt, Radhakrishnan, Jindal, Devadoss, & Dhar, 2014;Higashi et al, 2014). Studies have demonstrated emergence of psychological changes in both men and women after establishment of infertility.…”
Section: Discussionmentioning
confidence: 99%